The Heuristics and Biases of Top Managers: Past, Present, and Future - Hodgkinson, Gerard P.; Burkhard, Barbara; Foss, Nicolai J.; Grichnik, Dietmar; Sarala, Riikka M.; Tang, Yi; Van Essen, Marc (Journal of management studies, 2023)
Psychology‐grounded research on heuristics and biases in decision making has become increasingly influential in the field of management studies. However, although this line of inquiry is recognized as a valuable perspective for advancing understanding of decision processes in the upper echelons of firms, extant research remains unbalanced, the bulk of previous endeavours having been focused on managerial overconfidence, with insights from more recent dual‐process theory and ecological rationality conceptions of heuristics less explored. This introductory article to the special issue of the Journal of Management Studies, entitled ‘the heuristics and biases of top managers: Past, present, and future’, offers a reflective review of prior work addressing its focal theme and places the articles incorporated into the special issue within this broader context. In addition, it sets out a number of directions for future work, with a view to inspiring the continuing advancement of conceptual and empirical knowledge and management practice.